Front Cover: Lanthanide DO3A‐Tropone Complexes: Efficient Dual MR/NIR Imaging Probes in Aqueous Medium (Eur. J. Inorg. Chem. 43/2017). Issue 43 (13th November 2017) - Hashami, Zohreh; Martins, Andre F.; Funk, Alexander M.; Jordan, Veronica Clavijo; Petoud, Stéphane; Eliseeva, Svetlana V.; Kovacs, Zoltan
Abstract : The Front Cover shows, at the center, the structure of a DOTA‐based ligand with a tropone coordinating sidearm. The ligand forms monohydrated lanthanide chelates. The Gd III complex is a good T 1 ‐shortening MRI agent, as illustrated in the blue field by the MR images of the kidneys and the liver of a mouse. The tropone unit is an efficient sensitizer for Nd III and Yb III, and the characteristic NIR emissions of these lanthanide ions (Nd in the green and Yb in the red field) were easily detected in aqueous solution despite the presence of the inner‐sphere water molecules. More information can be found in theCommunication by S. V. Eliseeva, Z. Kovacs et al. For more on the story behind the cover research, see theCover Profile .